Preservation of hippocampal ultrastructural constituents with Nigella sativa oil treatment to rats challenged by global cerebral oligemia - Azzubaidi, Marwan Saad; Talib, Norlelawati A.; Saxena, Anil Kumar; Ahmed, Qamar Uddin; Al-Ani, Imad Matloub Dally (2013)
The oil extract of Nigella sativa seeds (NSO) was found to preserve viability of cerebellar neurons in vitro. Recent in vivo experimental study proved that NSO daily oral treatment was able to prevent memory and learning deterioration in a murine model of mild global cerebral ischemia (MGCI) that was created with permanent bilateral occlusion of the common carotid arteries (2VO) in rats. The current study’s object ive was to assess the effect of NSO treatment on pyramidal and other neighboring neurons within CA1 hippocampal subfield of rats with MGCI that was achieved through 2VO procedure. The assessment was ultrastructural using transmission electron microscopy (TEM). Nine rats were equally divided into three groups: sham control, untreated 2VO and NSO treated group (2VO with daily oral NSO treatment). By the end of the 10th postoperative week coronal sections of the hippocampus were collected and processed for transmission electron microscopy (TEM). The neurodegenerative changes observed in pyramidal cells, astrocytes, endothelial basement membrane and axoplasms of CA1 hippocampal region of 2VO group were completely absent in sham operated control group. Meanwhile, NSO treated groups were almost free of ultrastructural neurodegenerative changes as those detected in untreated 2VO group. This adds another supporting evidence of the promising neuroprotective activity provided by NSO treatment to prevent age related neurodegenerative diseases especially those associated with chronic global cerebral hypoperfusion such as Alzheimer’s disease.